A new method of assessing airways and selecting the method of tracheal intubation in patients with burns of face and neck during planned surgery - A. V. Korneev; S. A. Orudzheva; A. N. Kudryavtsev; A. A. Ponomarev (Вестник анестезиологии и реаниматологии)
Patients with burns of the face and neck are more likely to develop unpredictable difficult airways, thus it is necessary to refine approaches to preoperative prediction of such a condition.The objective: develop a method for airway assessment in patients with burns of the face and neck that can improve the results of tracheal intubation by reducing the incidence of unpredictable difficult airways.Subjects and methods. This study was based on analysis of retrospective (42 patients) and prospective (42 patients) data. At the retrospective stage, before surgery all of the patients had their airways assessed as per El-Ganzouri scale. Based on the results, a cumulative rating scale (CRS) was developed, which effectiveness was assessed by prospective data.Results. The area under the ROC curve was 0.67 (p = 0.027). Sensitivity, specificity, positive predictive value, and negative predictive value made 100%, 37%, 45,2%, and 100% accordingly. The assessment of the newly developed CRS: the area under ROC curve was 0.96 (p ≤ 0.05). Sensitivity, specificity, positive predictive value, and negative predictive value made 90.9, 100, 100, and 96.8% accordingly.Conclusion: The developed cumulative rating scale (CRS) has a better predictive potential for assessing the airways in patients with burns of face and neck versus traditional approaches.